COMPETENCY PERSPECTIVE IN EDUCATIONAL PHILOSOPHY - Suparjo Suparjo (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Empowerment of MSMEs is very strategic, because of its great potential in driving the economic activities of the community, and at the same time being the main source of income for the majority of the community in improving their welfare. MSME competence is important because it will increase MSME productivity and performance. One of the ways to increase the competence of SMEs is through learningPhilosophy of Education. The purpose of this research is toDescribe the role of educational philosophy in the development of human resources.